Literatura brasileira: do átomo ao bit - Gimenes, Roseli (2016)
The main aim of this work is to feature the development of Brazilian literature considering principally, and from the nineteenth century onwards, the so-called literature of invention such as Memórias Póstumas de Brás Cubas by Machado de Assis, analyzing diachronically and synchronically the works of Gregório de Matos, during the Baroque period, Tomás Antonio Gonzaga, during Arcadismo, Oswald de Andrade during Modernism and, in the contemporary scene, the book A festa by Ivan Angelo, in terms of its interaction with the printed book, to finally focus on the cyberliterature by Clarah Averbuck, and the concrete and digital poetry by Augusto de Campos. When looking for the signs of printed and digital narratives in Brazilian literature, certain conclusions can be reached that show a poetry of invention and interaction, the influence of concrete poetry in cyberliterature as well as the marks of concretism in hyper digital short stories. As regards the teaching of literature, even in Distance Education, we have as our aim to observe the cognitive process of the students of Portuguese at university level, in private institutions, and their relationship with printed and digital narratives when studying Brazilian literature. This work also has as one of its hypotheses to prove the relevance of poetic works created by computers and having artificial intelligence as their starting point. This kind of literary works already foreshadows robots that tell stories, participate in scientific actions, and win chess matches, at the time that create meaningful narratives that will, eventually substitute poetic works, among other human actions and emotions. This part of the research was based on the works of theoreticians, such as John Searle who, with his metaphoric experience of The Chinese Room argued against strong artificial intelligence, and Roger Schank who, through the observation of children and, opposing Searle´s theories, believes in the learning process carried out by machines. The theoretical readings that vied the present research and conclusions on literature and the new technologies found inspiration, in particular, in the works of Lucia Santaella and her concept of “extended literature” and literature in the web, the works of contemporary literary theory critics such as Haroldo de Campos and Augusto de Campos, as well as the already canonical works on literary theory, for the analysis of printed works, prior to cyber literature by Alfredo Bosi, Antonio Cândido and Marisa Lajolo, among others, which waver in between the printed and the digital. It is to be expected that the discovery that creation, invention and interaction are inherent to poetical literary works will inspire teachers of Brazilian literature in their also inventive, creative and interactive interpretations done in class, in turn leading their students to surf the social medias, like blogs, magazines and literary sites, not only in search of entertainment but also of knowledge